Does fathers' and mothers' rumination predict emotional symptoms in their children?. (14th August 2017) - Psychogiou, Lamprini; Moberly, Nicholas J.; Parry, Elizabeth; Russell, Abigail Emma; Nath, Selina; Kallitsoglou, Angeliki
Abstract : Objectives: Although rumination can have a negative influence on the family environment and the quality of parent–child interactions, there is little research on the role of parental rumination in predicting adverse child outcomes over time. This longitudinal study examined whether mothers' and fathers' brooding rumination would each uniquely predict emotional symptoms in preschool children. Methods: The initial sample consisted of 160 families (including 50 mothers with past depression, 33 fathers with past depression, and 7 fathers with current depression according to the Structural Clinical Interview for DSM‐IV). Families were seen at two times separated by 16 months. Children's mean age at the entry into the study was 3.9 years ( SD  = 0.8). Each parent independently completed the Ruminative Response Scale, the Child Behavior Checklist, the Patient Health Questionnaire, and the Dyadic Adjustment Scale. Results: Fathers' brooding rumination significantly predicted children's emotional symptoms over 16 months when controlling for child emotional symptoms, couple adjustment, parents' depressive symptoms, mothers' brooding and reflective rumination, and fathers' reflective rumination at baseline. Unexpectedly, mothers' brooding rumination did not significantly predict child emotional symptoms over time. Correlational analyses showed significant associations between parents' rumination and lower levels of couple adjustment. Conclusions: Findings suggest that fathers' brooding rumination may play a unique role in their children's emotional outcomes. If these findings are replicated, studies should examine the processes by which these links occur and their implications for clinical interventions. Practitioner points: Rumination is prevalent among individuals with depression, but to date no studies have examined the possible role of mothers' and fathers' brooding rumination in predicting children's emotional symptoms. Fathers' brooding rumination was positively associated with children's emotional symptoms over time when controlling for mothers' rumination and other important characteristics. Parental rumination might be a promising target for both prevention and intervention strategies for parents with depression and their children. The findings of this study could inform parenting interventions (e.g., educate parents about the possible effects of rumination on family interactions and children's outcomes, help parents notice when they ruminate, teach them to replace rumination with more adaptive strategies). The findings should be interpreted with caution. The study relied on self‐reports, and therefore, the data are subject to shared method variance which may have artificially inflated associations between parent and child outcomes. The sample consisted of well‐educated parents, and therefore, the findings should be generalized to other populations with caution.